BRAND NAME AND MILLENNIAL GENERATION ON CUSTOMER PREFERENCES THEIR IMPACT ON BRAND LOYALTY IN MSMEs - Eman Sulaiman; Weni Novandari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study analyzes and finds out the influence of brand name and millennial generation on consumer preferences and their impact on brand loyalty in MSMEs. The data analysis technique uses descriptive analysis and questionnaire feasibility tests that have been tested beforehand with validity tests, reliability tests, multicollinearity tests, coefficients of determination and Path Analysis using Smart PLS with a total sample size of 93 respondents. The results of the direct influence study: show that the brand name has a negative and insignificant effect on Brand Loyalty. Brand Name has a negative and insignificant effect on Customer Preference, Customer Preference has a positive and significant effect on Brand Loyalty, that Millennial Generation has a negative and insignificant impact on Customer Preference. While the indirect effect: Brand Name has a negative and insignificant effect on Brand Loyalty, Millennial Generation has a positive and significant effect on Brand Loyalty.